Neutron Tomography as a Tool to Study Immiscible Fluids in Porous Media without Chemical Dopants - Schröter, Matthias; Murison, Julie; Moosavi, Robabeh; Schulz, Michael; Schillinger, Burkhard (Energy & Fuels, 2015)
We present the first study of fluid distribution inside porous media imaged by neutron tomography. We demonstrate that this technique has matured sufficiently to deliver pore level results. The major advantage of neutron tomography is the contrast mechanism of using deuterated phases. This allows high contrast imaging without the need to add large amounts of inorganic salts as dopants, required to achieve adequate contrast for X-ray tomography studies. Measurements were performed at the Antares beamline (MLZ, Garching) with a voxel size of 11.8 μm. We propose this technique as a useful tool for studying mutliphase phenomena in porous media where the results are known to depend on the salinty and species of ions present, such as low salinity water, surfactant, and polymer flooding.